DEVELOPMENT AND ENTREPRENEURSHIP TRAINING FOR STUDENTS OF DAARUNNAJAH ASHIDDIQIYYAH ISLAMIC BOARDING SCHOOL, MAJALENGKA REGENCY, WEST JAVA - Arief, Dede Zainal; Widiantara, Tantan; Hervelly, Hervelly; Ghaffa, Rizal Maulana; Habibah, Sindi; Abdullah, Rangga; Yulianti, Ana; Imannuddin, Kemas Ramadhani (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
In this community service activity, entrepreneurship training in the field of processed food industry is carried out for students and teachers. The types of processed food given as training materials are types of processed food that utilize the potential of local raw materials around the implementation site. These materials are the result of research that has previously been conducted, but has not been implemented. Participants have followed with enthusiasm and consider the knowledge gained to be very useful as a provision to improve family welfare. The boarding school made the activity a provision of additional knowledge for the students. In addition to knowledge related to religious knowledge, understanding the material from the training will also be implemented to increase other sources of income besides the funds that have so far only come from student fees. The existence of the boarding school located in Sindanglama Village, Malausma District, Majalengka Regency has become a concern of the surrounding community. This can be seen from the visits of several figures during the training. Thus, the overall program in the short term has succeeded in achieving its objectives, while for the long-term further assistance is still needed for participants in order to realize a successful entrepreneurial unit.